2018
DOI: 10.3389/fchem.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Longevity of Antibody in Paper-Based Blood Typing Diagnostics

Abstract: Paper-based diagnostics provide a low-cost, reliable and easy to use mode of blood typing. The shelf-life of such products, however, can be limited due to the reduced activity of reagent antibodies sorbed on the paper cellulose fibers. This study explores the effects of aging on antibody activity for periods up to 12 months on paper and in solution under different aging and drying conditions—air-dried, lyophilized, and kept as a liquid. Paper kept wet with undiluted antibody is shown to have the longest shelf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…False negative reporting was also studied, and it was seen that antibody in liquid form had swelling of cellulose fibers due to moisture content that decreased erythrocyte adhesion to paper; thus the occurrence of a false positive was low, while air-dried antibodies and lyophilized antibodies showed false positive results after 9 months. Increased BSA concentration reduced protein (antibody) adsorption resulting in better flow, and thus a clearer negative was obtained for BSA diluted antibodies . Hertaeg et al explored a paper-based device for reverse typing using paper towel and hand sheet as the substrate for the detection of IgM blood typing antibodies and SARS CoV-2 antibodies.…”
Section: Different Paper Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…False negative reporting was also studied, and it was seen that antibody in liquid form had swelling of cellulose fibers due to moisture content that decreased erythrocyte adhesion to paper; thus the occurrence of a false positive was low, while air-dried antibodies and lyophilized antibodies showed false positive results after 9 months. Increased BSA concentration reduced protein (antibody) adsorption resulting in better flow, and thus a clearer negative was obtained for BSA diluted antibodies . Hertaeg et al explored a paper-based device for reverse typing using paper towel and hand sheet as the substrate for the detection of IgM blood typing antibodies and SARS CoV-2 antibodies.…”
Section: Different Paper Substratesmentioning
confidence: 99%
“…Increased BSA concentration reduced protein (antibody) adsorption resulting in better flow, and thus a clearer negative was obtained for BSA diluted antibodies. 70 Hertaeg et al explored a paper-based device for reverse typing using paper towel and hand sheet as the substrate for the detection of IgM blood typing antibodies and SARS CoV-2 antibodies. Reagent blood cells were mixed with the patient's plasma, which contains the antibodies to be identified and deposited on paper.…”
Section: Different Paper Substratesmentioning
confidence: 99%
“…Through a glutaraldehyde cross-linking agent, the antibodies showed enhanced binding activity to the target when compared to the periodate oxidation method [ 97 ]. Other methods for antibody immobilization on a paper with shelf-life up to 12 months have been described [ 98 , 99 ]. Polyclonal antibodies have multiple binding sites, each specific to a particular antigen.…”
Section: Recognition Elementmentioning
confidence: 99%
“…Though paper-based diagnostics are reliable and costeffective, the shelf-life of such products is of concern to many users. A study was done to examine the effects of aging on antibody activity on paper and in solutions under different aging and drying conditions such as airdried, lyophilized, and kept as a liquid [30] . It showed that paper kept wet with undiluted antibodies has the longest shelf-life and the clearest reading.…”
Section: Microfluidic Paper-based Analytical Device (µPad)mentioning
confidence: 99%